The ballad of Laurel Springs [large type] - Beard, Janet (Thorndike Press large print core, 2021)
Ten-year-old Grace is in search of a subject for her fifth-grade history project when she learns that her four times-great grandfather once stabbed his lover to death. His grisly act was memorialised in a murder ballad, her aunt tells her, so it must be true. But the lessons of that revelation - to be careful of men, and desire - are not just Grace's to learn. Her family's tangled past is part of a dark legacy in which the lives of generations of women are affected by the violence immortalised in folksongs like 'Knoxville Girl' and 'Pretty Polly' reminding them always to know their place - or risk the wages of sin. Janet Beard's stirring novel, informed by her love of these haunting ballads, vividly imagines these women, defined by the secrets they keep, the surprises they uncover and the lurking sense of menace that follows them throughout their lives. With the same rich sense of place as Bloodroot or Serena, The Ballad of Laurel Springs is an unforgettable portrait of women fighting to make a safe place in the world for themselves and the people they love.